2008
DOI: 10.1590/s1413-86702008000500002
|View full text |Cite
|
Sign up to set email alerts
|

Lamivudine for chronic hepatitis B: a brief review

Abstract: Until recently, the only generally approved treatment for chronic hepatitis B was alpha-interferon; however, it gives only moderate efficacy in terms of sustained response (biochemical, virological and histological). In fact, only 20% to 40% of treated patients respond to therapy, with lower percentages (~ 10%) among patients infected with precoremutant strains of HBV (HBeAb HBV-DNA positive). The FDA of the USA approved the use of lamivudine in adult patients affected by chronic hepatitis B in 1998. In this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Lamivudine has been shown to be an effective antivirus drug for HBV infection in numerous studies . Our data also showed that using lamivudine 100 mg daily for prophylaxis could be protective against HBV reactivation in occult HBV carriers.…”
Section: Discussionsupporting
confidence: 71%
“…Lamivudine has been shown to be an effective antivirus drug for HBV infection in numerous studies . Our data also showed that using lamivudine 100 mg daily for prophylaxis could be protective against HBV reactivation in occult HBV carriers.…”
Section: Discussionsupporting
confidence: 71%
“…Amphotericin B and its lipid formulation proved to be very effective in the treatment of leishmaniasis, but the cost of this drug is still prohibitively high and out of the reach of poor people. More recently, the alkyl-phospholipid miltefosine [7] has emerged as an oral drug that is highly effective in children but occasionally presents gastrointestinal complications and also shows teratogenic effects. Edelfosine [8], another alkyl-phospholipid, has also been tested and was found to display a higher in vitro activity than miltefosine.…”
Section: Introductionmentioning
confidence: 99%
“…CHB infection has severe long-term outcomes and could contribute to hepatocellular carcinoma (HCC) cases [3]. It is estimated that CHB is among the ten leading causes of death worldwide [4]. The cost of health care, resulting in loss of life and productivity therefore has remarkable impact on the society.…”
Section: Introductionmentioning
confidence: 99%